Temperature and Time Optimization of Dragon Fruit Peel Powder Drying Using the Response Surface Methodology - Indrian, Oppy Valencia; Setiawan, Andika Putra; Wardhana, Danu Indra (Universitas Muhammadiyah Jember, 2024)
The purpose of this study is to obtain the right temperature and time for the manufacture of dragon fruit peel powder and to obtain the optimal total yield and water content. The method used in the spraying process is Foam Mat Drying. The method used for optimization is the Response Surface Method (RSM) with a factorial centralized composite design 22. The factors used are the temperature of 60°C, 70°C, and 80°C and the time is 5 hours, 6 hours, 7 hours. The results showed that the composition of the formula was the best at a temperature of 79,214°C and a time of 5,007 hours. It can be predicted that the optimal formula gets a yield value of 16.109%, and a moisture content of 4.662%. The total powder obtained in 1 day of production is 5000 grams, if the production for 1 week is 35,000 grams, then 150,000 grams will be obtained for 1 month of production. It was concluded that the optimal formula that has been obtained can be used as a model for making powder from dragon fruit peel.